Comprehensive profiling of lysine acetylproteome analysis reveals diverse functions of lysine acetylation in common wheat - Zhang, Yumei (Sci Rep, 2016)
Lysine acetylation of proteins, a dynamic and reversible post-translational modification, plays a critical regulatory role in both eukaryotes and prokaryotes. Several researches have been carried out on acetylproteome in plants. However, until now, there have been no data on common wheat, the major cereal crop in the world. In this study, we performed a global acetylproteome analysis of common wheat variety (Triticum aestivum L.), Chinese Spring. In total, 416 lysine modification sites were identified on 277 proteins, which are involved in a wide variety of biological processes. Consistent with previous studies, a large proportion of the acetylated proteins are involved in metabolic process. Interestingly, according to the functional enrichment analysis, 26 acetylated proteins are involved in photosynthesis and Calvin cycle, suggesting an important role of lysine acetylation in these processes. Moreover, protein interaction network analysis reveals that diverse interactions are modulated by protein acetylation. These data represent the first report of acetylome in common wheat and serve as an important resource for exploring the physiological role of lysine acetylation in this organism and likely in all plants.